Metaverse influencer marketing and consumer purchase decision: A study of selected real estate companies in South-South Nigeria - Iyadi, Rollins Chiyem; Eboh, Mercy Ebele; Olannye, Henry Odigwe; Edeme, Nelson Chidi; Onuorah, Anastasia Chi-Chi (Edelweiss Applied Science and Technology, 2025)
This research examined the impact of metaverse marketing on consumer purchase decisions for real estate enterprises in southern Nigeria. This research is quantitative. Studies were conducted with a sample group of 374 respondents who patronize these real estate firms. The data were analyzed using Ordinary Least Squares (OLS) multiple regression. The study reported that virtual events, metaverse content development, and virtual influencers influence consumers’ purchase decisions both positively and significantly. Hence, the study submits that for the sampled firms to increase repeat purchases, their virtual influencers should be integrated into immersive metaverse experiences.